Inferior Epigastric Artery Pseudoaneurysm Following Paracentesis in a Liver Graft Recipient: A Case Report - Ebrahimi, Amir Pasha (Iran J Radiol, 2015)
Pseudoaneurysm happens when the artery wall is injured and the blood is contained by the surrounding tissues with eventual formation of a fibrous sac communicating with the artery. We report a case of a 39-year-old man with inferior epigastric artery (IEA) pseudoaneurysm after paracentesis. The pseudoaneurysm was diagnosed by Doppler ultrasound and treated by surgical intervention regarding the patient’s underlying comorbidity. IEA false aneurysm must be included in the differential diagnosis during investigation of the cause of any swelling after paracentesis. Cirrhotic patients may be more prone to this complication because of thin rectus muscle that could not confine the hematoma.